2017
DOI: 10.3390/su9050729
|View full text |Cite|
|
Sign up to set email alerts
|

Using Analytic Hierarchy Process to Examine the Success Factors of Autonomous Landscape Development in Rural Communities

Abstract: Abstract:The absence of comprehensive plans has resulted in disordered rural development and construction and a mix of new and old buildings in rural communities. Disorganized and blighted spaces have become rural landscape obstacles. After the Rural Rejuvenation Act was passed, rural construction has been guided with plans, and the government expects to enhance surroundings and expand policies through autonomous community development to create a good rural landscape. Through a literature review, this study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Zhu et al applied a Principal Component Analysis (PCA) and Grey Entropy measurement model to evaluate urban-rural coordination by considering the indices of economic, social security, public services, and environmental quality [35]. Liang and Peng used AHP to examine the success factors of autonomous landscape development in rural areas, covering 8 criteria and 28 sub-criteria [36]. Using GIS, Masot and Alonso analyzed the 25 years of European rural development policy through LEADER approach to reduce the differences between rural and urban areas, as well as to satisfy the basic needs of population [37].…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al applied a Principal Component Analysis (PCA) and Grey Entropy measurement model to evaluate urban-rural coordination by considering the indices of economic, social security, public services, and environmental quality [35]. Liang and Peng used AHP to examine the success factors of autonomous landscape development in rural areas, covering 8 criteria and 28 sub-criteria [36]. Using GIS, Masot and Alonso analyzed the 25 years of European rural development policy through LEADER approach to reduce the differences between rural and urban areas, as well as to satisfy the basic needs of population [37].…”
Section: Introductionmentioning
confidence: 99%
“…The AHP approach also allows researchers to examine the weight and rank of each indicator (e.g., FD1, FS2 or OE2) in the overall sustainable agriculture (SUST)—hereafter named the “overall weight” and “overall rank,” respectively. The overall weights are computed as the products of the weights from each level of the hierarchy system (Liang & Peng, 2017). For example, the overall weight of Temporal diversity of crops (FD3) is 0.002 and is calculated according to Table 6 below.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Rezaei‐Moghaddam and Karami (2008) used AHP to examine the important factors within the economic, social and ecological criteria that can affect the agriculture development in Iran. Similarly, Liang and Peng (2017) identified that manpower input is the most important factor whilst geographic location is the least important one in the autonomous landscape development of rural communities in Taiwan. In Greece, Bartzas and Komnitsas (2020) designed an environmental AHP model to identify the most sustainable agricultural management practices at regional level whilst Tzouramani, Mantziaris, and Karanikolas (2020) examined the sustainability performance at the farm level.…”
Section: Introductionmentioning
confidence: 99%
“…This study referred to the number of key success factors put forward by several researchers [33], who suggested that each industry has two to six factors that determine whether it can be successful, and these factors must be maximized if a company or industry wants to succeed. According to the results of this study, as shown in Table 4, the difference between the sixth (0.0729) and the seventh (0.0718) values of the integrated weight ranking is very small, and there is a large gap between the seventh (0.0718) and the eighth (0.0570) values.…”
Section: Discussionmentioning
confidence: 99%